Development of erosion equation and numerical simulation methods with the consideration of applied stress. (September 2019) - Wang, Huakun; Yu, Yang; Yu, Jianxing; Wang, Zhaoyu; Li, Haoda
Abstract: Damage induced by erosion-corrosion is the main cause of pipeline failure. In this study, the effect of erosion caused by particles entrained in the conveying fluid was investigated. A new erosion equation that considers the effect of applied load on erosion ratio ( ER ) was established based on available test data and on the E/CRC erosion equation. A lognormal form for the angle function was found to be more concise and accurate for cases without stress (caused by operating loads), and the stress induced erosion acceleration effect was described by exponential function. A novel numerical simulation method was also proposed that combines the proposed stress-dependent erosion equation with the commercial software COMSOL Multiphysics, providing new ways of understanding erosion behavior and predicting erosion damage in oil and gas pipelines. Highlights: A new erosion equation that considers the effect of applied load on erosion was established. A lognormal form for the angle function is more concise and accurate. A novel numerical simulation method that considers the effect of applied load on erosion was proposed.